2019
DOI: 10.1063/1.5123786
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure factor of a lipid bilayer in the presence of a high electric field

Abstract: The influence of a high average electric field (∼1 V/nm) in the hydrophobic interior of a bilayer lipid membrane on short-wavelength in-plane phononic motions of lipid chains is considered. The average electric field is assumed to be nearly constant on a picosecond time scale and a nanometer length scale. This field may be induced, for instance, by externally applied subnanosecond electric pulses or the membrane dipole potential. Using a generalized hydrodynamic approach, we derive a corresponding electrohydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…However, the lack of a clear pinched hysteresis, in both cases, is likely due to the time-domain current signal (Figure 4a) becoming saturated with perturbations from over 40 separate sinusoidal waveforms (see Figure 2). Similar behavior has been reported for several electrochemical systems, both in the time domain using I-E scans, [32][33][34] and in the frequency domain with EIS, [35] and have been attributed to capacitively and inductively coupled memristive models. We also note that we had previously reported zero-crossing pinched hysteresis in the I-E and the q-E planes for the same DPhPC DIBs system as studied here, as expected for voltage-controlled memristive and memcapacitive systems.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…However, the lack of a clear pinched hysteresis, in both cases, is likely due to the time-domain current signal (Figure 4a) becoming saturated with perturbations from over 40 separate sinusoidal waveforms (see Figure 2). Similar behavior has been reported for several electrochemical systems, both in the time domain using I-E scans, [32][33][34] and in the frequency domain with EIS, [35] and have been attributed to capacitively and inductively coupled memristive models. We also note that we had previously reported zero-crossing pinched hysteresis in the I-E and the q-E planes for the same DPhPC DIBs system as studied here, as expected for voltage-controlled memristive and memcapacitive systems.…”
Section: Resultssupporting
confidence: 82%
“…It has been suggested that stress, which can be induced electrostatically through surface charge storage, is a driver for ion channel induction. [34][35][36][37] The fact that τ increases with increases in bias voltage suggests that additional energy must be expended to initiate surface charging, implying that interfacial ions respond in a kinetically slow fashion to strong interfacial forces. Indeed, ion-pairing and related interfacial interactions are essential to the assembly of soft-matter systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that the collective dynamics of phospholipid bilayers plays an important role in cellular membrane mechano-transduction (i.e., the conversion of a mechanical stimulus into electrochemical activity) and the transmembrane passive transport of protons, water, ionic solutes, and other small molecules. , Currently, it is an open question as to how molecular stress is distributed in membranes and how it propagates to influence membrane-bound mechano-sensitive macromolecules, such as enzymes and ionic channels, to name a few. Moreover, the onset of stress-driven processes remains practically unexplored .…”
Section: Introductionmentioning
confidence: 99%
“…We earlier described one possible electroporation mechanism that consists in the formation of large amplitude density fluctuations on subnanometer length scales in the hydrophobic region of a lipid bilayer due to the impact of electric pulses [13,14]. Here, we argue that the formation of large amplitude, subnanometer density fluctuations in lipid bilayers, induced by high-intensity pulsed electric fields with picosecond durations, may produce lipid nanopores and change transmembrane transport with subsequent cellular responses, which could be of interest for the development of electroporation biotechnologies.…”
Section: Introductionmentioning
confidence: 99%